Analisis Spasial Bayesian dengan Metode CAR Leroux (Studi Kasus: Stunting di Indonesia) - Muthahharah, Isma; Mar’ah, Zakiyah (Journal of Mathematics, Computations and Statistics, 2024)
Stunting has become a problem that has received special attention and is an urgent priority for the international community. Stunting or chronic malnutrition is a nutritional problem caused by malnutrition from food that lasts for a long time. The purpose of this study is to map the relative risk (RR) of stunting cases in Indonesia. This type of research is quantitative research. The data used are stunting cases that occurred in 2023 in Indonesia. The method used is Spatial Bayesian with the CAR Leroux Method. The selection of the best model is based on model suitability criteria, such as Watanabe Akaike Information Criterion (WAIC) and Deviance Information Criterion (DIC). The results of the analysis show that the best model obtained in the RR model of stunting cases in Indonesia shows that the CAR Leroux model with a higher GI (0.1; 0.1) is suitable for modeling the growth rate pattern of confirmed stunting cases in Indonesia. The three provinces with the highest RR values ​​are West Sulawesi Province, West Kalimantan Province, and East Nusa Tenggara Province. While the three provinces with the lowest RR values ​​are DKI Jakarta Province, South Sumatra Province, and North Sulawesi Province.